Painting as a Pastime, 1932 - Churchill, Winston (Essays and Other Works., 2014)
The first volume in a collection essays and journalism from the legendary politician and Nobel Prize-winning author explores his artistic pursuits. Legendary politician and military strategist Winston S. Churchill was a master not only of the battlefield, but of the page and the podium. Over the course of forty books and countless speeches, broadcasts, news items and more, he addressed a country at war and at peace, thrilling with victory but uneasy with its shifting role on the global stage. In 1953, he was awarded the Nobel Prize for Literature for "his mastery of historical and biographical description as well as for brilliant oratory in defending exalted human values." During his lifetime, he enthralled readers and brought crowds roaring to their feet; in the years since his death, his skilled writing has inspired generations of eager history buffs. Best known for his political genius and keen eye for military tactics, Churchill was a man of many talents-not the least of which was painting. Throughout his life, Churchill painted to relieve his mind from the demands of leadership and to keep the "black dog" of depression at bay. Included in this volume are Churchill's meditations on painting as a salve for the spirit and an essential creative pursuit. His love for the craft comes to life in this concise yet impassioned work. This volume includes eighteen reprints of Churchill's original work in oil, giving the reader a window into the little-known creative and artistic skill of this prominent figure in twentieth century history.